Hazard-based risk grouping effectively stratifying breast cancer patients in post-irradiation long-term heart diseases: a population-based cohort study - Lee, Moon-Sing; Tsai, Wei-Ta; Yang, Hsuan-Ju; Hung, Shih-Kai; Chiou, Wen-Yen; Liu, Dai-Wei; Chen, Liang-Cheng; Chew, Chia-Hui; Yu, Ben-Hui; Hsu, Feng-Chun; Wu, Tung-Hsin; Lin, Hon-Yi (Frontiers in Cardiovascular Medicine, 2023)
Background Even though advanced radiotherapy techniques provide a better protective effect on surrounding normal tissues, the late sequelae from radiation exposure to the heart are still considerable in breast cancer patients. The present population-based study explored the role of cox-regression-based hazard risk grouping and intended to stratify patients with post-irradiation long-term heart diseases. Materials and Methods The present study investigated the Taiwan National Health Insurance (TNHI) database. From 2000 to 2017, we identified 158,798 breast cancer patients. Using a propensity score match of 1:1, we included 21,123 patients in each left and right breast irradiation cohort. Heart diseases, including heart failure (HF), ischemic heart disease (IHD), and other heart diseases (OHD), and anticancer agents, including epirubicin, doxorubicin, and trastuzumab, were included for analysis. Results Patients received left breast irradiation demonstrated increased risks on IHD (aHR, 1.16; 95% CI, 1.06-1.26; p < 0.01) and OHD (aHR, 1.08; 95% CI, 1.01-1.15; p < 0.05), but not HF (aHR, 1.11; 95% CI, 0.96-1.28; p = 0.14), when compared with patients received right breast irradiation. In patients who received left breast irradiation dose of >6040 cGy, subsequent epirubicin might have a trend to increase the risk of heart failure (aHR, 1.53; 95% CI, 0.98-2.39; p = 0.058), while doxorubicin (aHR, 0.59; 95% CI, 0.26-1.32; p = 0.19) and trastuzumab (aHR, 0.93; 95% CI, 0.33-2.62; p = 0.89) did not. Older age was the highest independent risk factor for post-irradiation long-term heart diseases. Conclusion Generally, systemic anticancer agents are safe in conjunction with radiotherapy for managing post-operative breast cancer patients. Hazard-based risk grouping may help stratify breast cancer patients associated with post-irradiation long-term heart diseases. Notably, radiotherapy should be performed cautiously for elderly left breast cancer patients who received epirubicin. Limited irradiation dose to the heart should be critically considered. Regular monitoring of potential signs of heart failure may be conducted.